White-collar crime: a statistical study on its common causes - Liew, Samuel Wei Siew; Puah, Chin Hong; Harry, Entebang (MultiCraft Limited, 2011)
White-collar crime has always managed to find its way to corrode the values and ethics that people have in a society. A statistical study was carried out to identify some of the common causes of white-collar crime in Malaysia. To pursue this, survey questionnaires were distributed to both potential and existing investors to assess their view regarding the matter. The study found that, one of the leading causes of white-collar crime in Malaysia is due to the fact that there is a belief that competitors are paying bribes to win contracts, and hence others follow suit. On the other hand, most perpetrators commit white-collar crime because there are many opportune moments for them to do so. Companies should, therefore, gear toward good governance structure and internal controls so as not to give potential and existing perpetrators opportunity to engage in any misdeed.